E-Book Development Guidelines for Creating Canva-Based Learning Media to Improve the Professional Competence of Elementary School Teachers - Tenggar Amrullah; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
Teachers' professional competence plays an important role in designing effective learning, utilizing technology, and developing innovative materials to improve the quality of teaching and student achievement in the era of modern education. This study aims to describe the assessment of material experts, media experts, and practitioners, and to analyze the effectiveness of developing an e-book guide to creating Canva-based learning media to improve the professional competence of elementary school teachers. In preparing the research, it is necessary to prepare several supporting instruments, including e-book validation instruments, test instruments, interview instruments, and a prototype of the final product in the form of an e-book guide to creating PowerPoint learning media using Canva for elementary school teachers. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Develop, Implement, and Evaluate). The research was conducted in the Wakhidin Sudirohusodo Cluster, Mandiraja District. Data collection used questionnaires, tests at the implementation stage, and interviews with experimental and control class strategies by holding training to produce products and measure the improvement of the professional competence of elementary school teachers.